2009
DOI: 10.2166/wh.2009.129
|View full text |Cite
|
Sign up to set email alerts
|

Free-living amoebae, Legionella and Mycobacterium in tap water supplied by a municipal drinking water utility in the USA

Abstract: Legionella and Mycobacterium can proliferate within free-living amoebae (FLA) where they are protected from disinfectants at concentrations that can kill bacteria but not protozoa. Despite effective treatment of drinking water, microbes can enter water utility distribution systems (DS) and hence the plumbing within building premises. Additionally, biofilm formation may account for the persistence of microbes in the DS. In the present study a domestic water tap in north-central United States (USA) was sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 64 publications
6
69
0
2
Order By: Relevance
“…The same source of water, which may supply domestic and clinical service providing premises, will also have nosocomial pathogens and amoebae prevalent within them [18,21,25,34,53], However, Hartmanella (Vermiformis) species are also reported to have been isolated from the throat of humans from as long ago as 1967 [54] implying that the high prevalence of V. vermiformis in the DUWL could also come from humans. This study, identified a clinical isolate of S. marcescens, from one out of 31 DUWL water samples.…”
Section: Vermiformis Dominates the Duwl Environment [7] And Their mentioning
confidence: 99%
See 2 more Smart Citations
“…The same source of water, which may supply domestic and clinical service providing premises, will also have nosocomial pathogens and amoebae prevalent within them [18,21,25,34,53], However, Hartmanella (Vermiformis) species are also reported to have been isolated from the throat of humans from as long ago as 1967 [54] implying that the high prevalence of V. vermiformis in the DUWL could also come from humans. This study, identified a clinical isolate of S. marcescens, from one out of 31 DUWL water samples.…”
Section: Vermiformis Dominates the Duwl Environment [7] And Their mentioning
confidence: 99%
“…Once inside the amoebal cell, some bacteria will survive or escape the adverse conditions presented by digestive vacuoles, but can also find sanctuary from unfavourable environmental conditions and can multiply [25]. Furthermore, bacteria such as S. aureus may be ingested, but released undigested and intact [39].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The general trend of tap water of proposed mixed origin to contain the highest number of the isolated bacteria concludes that treatment against microbes in water plants was not highly effective. In addition, microbes can enter water utility distribution systems and biofilm formation may account for the persistence of microbes in the distribution systems [40]. The walls of the pipes in the distribution system provide ideal surfaces for microbial colonization [41].…”
Section: Discussionmentioning
confidence: 99%
“…Their presence represents a double threat to human health, being also related to amoeba-resisting bacteria, such as Legionella spp. and Mycobacterium spp., which proliferate in protozoa thus increasing the probability of causing diseases in humans (Marciano-Cabral et al, 2010). Some protozoa, for example Giardia spp.…”
Section: Occurrence Of Protozoa In Drinking Water and Associated Biofmentioning
confidence: 99%